Science and the farm - Brooks, Karen (Brookings Institution, 2017)
Africa’s youth employment issue is fundamentally one of agricultural modernization and investment in science. Farming remains the dominant occupation of most young Africans; this despite the fact that few respond “I want to be a farmer” when asked about their aspirations. More youths remain on farms than leave, although the movement away is very visible and has raised concern about food security, aging of the countryside, and excessive dependence on food imports. Concerns would be best directed toward understanding the needs of young people who stay on farms, already a large group that will grow as the global slowdown and attenuation of the commodity boom affect the continent. The agriculture that will allow young farmers to prosper will have to draw on the best of modern agricultural science—and at present it does not.